Identification of founder and novel mutations that cause congenital insensitivity to pain (CIP) in palestinian patients - Boushra Khaled; Mahmoud Alzahayqa; Ahmad Jaffal; Husam Sallam; Rua'a Thawabta; Mamoun Mansour; Akram Alian; Zaidoun Salah (BMC, 2023)
Abstract Background Congenital insensitivity to pain (CIP) is a rare autosomal recessive disorder characterized primarily by an inability to perceive physical pain from birth, resulting in the accumulation of bruising, inflammation, and fractures that affect patient's life expectancy. CIP has different forms including CIP and CIPA. CIP with Anhidrosis (CIPA) is the most common type of CIP, which is caused mainly by mutations in NTRK1 and NGF genes, and is characterized by mental retardation and the inability to sweat (Anhidrosis). Because of high consanguinity rates in Palestine, this rare disease appears to have a higher frequency than in other communities. However, there were no systematic studies to address the genetic factors that cause CIP in the Palestinian community. Methods In our study, we used Sanger and Whole exome sequencing to genotype members of five CIP-affected Palestinian families. Results Our results confirm the presence of the founder c.1860-1861insT mutation in the NTRK1 gene of Palestinian Bedouin CIPA patients. Furthermore, one CIPA family carried a missense c.2170 G > A (G724 S) mutation in exon 16 of the NTRK1 gene. Finally, a novel nonsense c.901 A > T mutation (K301*) was detected in exon 7 of the SCN9A gene in CIP without anhidrosis family. Conclusions Our study revealed three mutations that cause CIP and CIPA in the Palestinian community, which can help in improving the process of diagnosis and genetic counseling and establishing protocols for the diagnosis and follow-up for the affected individuals. This is especially important given that early diagnosis and medical care interference can prevent unpleasant CIP and CIPA complications.